Shredding Paper : The Rise and Fall of Maine's Mighty Paper Industry - Hillard, Michael G. (Book collections on Project MUSE., 2020)
"From the early twentieth century until the 1960s, Maine was the nation's leading producer of paper, with companies like Great Northern Paper, Oxford Paper and S. D. Warren owning more than half of the state's land, running company towns, and dominating politics throughout the state. But by the 1980s, the workforce was less than a quarter of what it once was. In this book, Michael G. Hillard details what happened to destroy the industry"--